Effectiveness Of TONJANGPIS (Tuna Fish And Banana Blossom Shredded Product) Training On DASHAT Cadres’ Knowledge And Skills In Stunting Prevention - Lam Murni br Sagala; Nelly Dameria Sinaga; Dior Manta Tambunan (International Journal of Health Engineering and Technology, 2026)
Stunting remains a major public health problem that requires community-based interventions and the utilization of local food resources. One of the innovations developed is TONJANGPIS shredded product (Tuna Fish and Banana Blossom Shredded Product), a nutritious local food with the potential to support stunting prevention efforts. This study aimed to analyze the effectiveness of TONJANGPIS production training in improving the knowledge and skills of Healthy Kitchen for Stunting Prevention (DASHAT) cadres. A quasi-experimental study with a one-group pretest-posttest design was conducted involving 50 DASHAT cadres in Belawan District. The intervention consisted of health education sessions, demonstrations, and hands-on training in TONJANGPIS production. Data were collected using knowledge questionnaires and skill observation sheets before and after the training. The results showed that cadres’ knowledge increased from 40% during the pretest to 90% during the posttest. Participants also demonstrated improved skills in processing, packaging, and promoting TONJANGPIS as a nutritious local food product. TONJANGPIS training was effective in enhancing the capacity of DASHAT cadres and can serve as a sustainable community empowerment strategy to support stunting prevention through the utilization of local food resources.